Deciphering consumer perceptions of Kisra prepared from biofortified and non-biofortified sorghum cultivars using the rate-all-that-apply (RATA) method - Sayed Abdelhalim, Tilal; Gobara Hamid, Manhal; Shaheen, Mazahir; Böhme, Claudia; Sir Elkhatim, Khitma A.; Idris, Yousif M. A.; Hamad, Mohammed; Muneer, Faraz; Rahmatov, Mahbubjon; Elsafy, Mohammed (Frontiers in Nutrition, 2025)
IntroductionMicronutrient deficiency remains a significant public health challenge in developing countries, including Sudan, particularly in rural areas, where access to a well-balanced diet is limited. This study evaluated consumer sensory acceptance and quality of Kisra, a traditional Sudanese fermented flatbread prepared from a combination of biofortified and non-biofortified sorghum cultivars.MethodsA panel of 100 assessors aged 18–75 evaluated nine Kisra products using hedonic overall liking and the rate-all-that-apply (RATA) technique.Results and discussionKisra made from the biofortified Dahab cultivar received the highest overall liking scores (~8, “like very much”), whereas blends such as Dahab + Dabar and Dahab + Arfa-gadamek showed moderate sensory acceptance (~7). Hierarchical agglomerative analysis grouped the assessors into three clusters comprising 50%, 26%, and 24% of the panel. Among the demographic factors, education level had the most significant influence on overall liking (51%), followed by consumption frequency (25.5%), and age (23.5%). The RATA model demonstrated a high assessor repeatability (0.994), homogeneity (0.904), and low global error (9.617). Sensory attributes, namely porousness, thickness, and sourness, were key drivers of preferences for Kisra made from Dahab. These findings underscore the effectiveness of RATA in the product and scaling biofortified Kisra to combat malnutrition and cater to diverse consumer preferences.